1998
DOI: 10.1038/sj.onc.1201907
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-614, the major autophosphorylation site of the receptor tyrosine kinase HEK2, functions as multi-docking site for SH2-domain mediated interactions

Abstract: HEK2 belongs to the family of EPH-related receptor tyrosine kinases (RTK) which are involved in axonal path®nding and the formation of the embryonic body plan. The knowledge about intracellular pathways of signal transduction mediated by EPH-related receptors is still limited. Many of the known key players of cellular signalling contain Src homology 2 (SH2) domains, which recognize phosphotyrosine motifs in RTKs. Thus, we examined the interactions of various SH2-containing molecules like PLC-g1, rasGAP, p85 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…Tyr-615 in EphA8 is located in the juxtamembrane domain and all known Eph-related receptors possess the corresponding tyrosine residue in their juxtamembrane domain (Figure 1). Previous studies indicated that phosphorylation at this conserved tyrosine residue mediates high a nity association with the SH2 domains of either the nonreceptor tyrosine kinases or Ras-GAP (Ellis et al, 1996;Holland et al, 1997;Hock et al, 1998;Zisch et al, 1998). Interestingly, EphA8 lacks the tyrosine residue corresponding to Tyr-596 in EphA4, which is also highly conserved and may modulate protein binding to its neighboring tyrosine residue (Figure 1) (Ellis et al, 1996).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Tyr-615 in EphA8 is located in the juxtamembrane domain and all known Eph-related receptors possess the corresponding tyrosine residue in their juxtamembrane domain (Figure 1). Previous studies indicated that phosphorylation at this conserved tyrosine residue mediates high a nity association with the SH2 domains of either the nonreceptor tyrosine kinases or Ras-GAP (Ellis et al, 1996;Holland et al, 1997;Hock et al, 1998;Zisch et al, 1998). Interestingly, EphA8 lacks the tyrosine residue corresponding to Tyr-596 in EphA4, which is also highly conserved and may modulate protein binding to its neighboring tyrosine residue (Figure 1) (Ellis et al, 1996).…”
Section: Resultsmentioning
confidence: 98%
“…It is not clear how the SH2 domains of nonreceptor tyrosine kinases discriminate between Eph receptors, but it is likely that additional nonconserved amino acids, in addition to the sequence motif identi®ed as the key site of interaction may provide the speci®city observed. It was recently proposed that the sequence divergence at position +5 relative to Tyr-614 in EphB3, the site corresponding to Tyr-615 in EphA8, might be crucial for determining the binding properties of Ras-GAP (Hock et al, 1998). For instance, the presence of an acidic amino acid such as glutamic or aspartic acid at position +5 determined the binding a nity to the amino-terminal SH2 domain of Ras-GAP as demonstrated in the cases of EphB1 and EphB3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations